Analisis Pola Persebaran Fasilitas Puskesmas di Kabupaten Pasaman Barat - Tirta Sari; Risky Ramadhan (Lembaga Yasin AlSys, 2026)
The imbalance between the availability of health facilities, service needs, and spatial inequality in the distribution of puskesmas (community health centers) can generate various adverse impacts for a region. This study aimed to analyze the spatial distribution of puskesmas in Pasaman Barat Regency using a Geographic Information System (GIS) to determine their distribution pattern and service coverage levels. A descriptive quantitative method with a spatial analysis approach was employed, with total sampling of all puskesmas in Pasaman Barat Regency. The distribution pattern was analyzed using the nearest neighbor analysis (NNA) method in ArcGIS software, with the nearest neighbor ratio, p-value, and z-score as key indicators. The results showed that the distribution pattern of puskesmas in Pasaman Barat Regency is uniform (dispersed), as indicated by a nearest neighbor ratio of 1.271242, a p-value of 0.020308, and a z-score of 2.320612. These values indicate that puskesmas are not clustered but are instead relatively evenly distributed across the entire area of Pasaman Barat Regency. In conclusion, this uniform distribution pattern reflects efforts to equalize the provision of health facilities, thereby potentially supporting improved equity in access to and coverage of health services for the community in Pasaman Barat Regency.